Pengaruh Status Quo Bias terhadap Resistensi Pengguna Alat Pembayaran Berbasis RFID di MRT Jakarta - Raka Echa Pratama; Diena Noviarini; Adnan Kasofi (INDO PUBLISHING, 2026)
The transformation of digital payment systems in public transportation has encouraged MRT Jakarta to implement Radio Frequency Identification (RFID) technology through the ALLRIDE Charm product. However, the adoption of this technology may generate user resistance. This study aims to analyze the effects of switching costs, switching benefits, and perceived value on user resistance toward the use of the RFID-based payment system ALLRIDE Charm in MRT Jakarta. This research employs a quantitative approach with a causal associative research design. Data were collected from 306 MRT Jakarta users through an online questionnaire using purposive sampling. Data analysis was conducted using Partial Least Squares–Structural Equation Modeling (PLS-SEM) with the assistance of SmartPLS software. The results indicate that switching costs and perceived value have a significant effect on user resistance, while switching benefits do not show a significant effect. These findings suggest that users’ perceptions of switching costs and perceived value are the primary factors influencing resistance to the adoption of RFID-based payment systems. In addition, this study develops an RFID reader application prototype as a practical contribution to support the implementation of ALLRIDE Charm. This research provides theoretical contributions to technology adoption studies in the context of public transportation and practical implications for MRT Jakarta in enhancing user acceptance of RFID-based payment systems.